Studi Literatur: Intensi Mengurangi Food Waste Behavior Ditinjau dari Theory of Planned Behavior - Anggraini, Ayu (Buletin Riset Psikologi dan Kesehatan Mental, 2024)
Food waste is a global issue that currently receives significant attention, and is included in the 12th Sustainable Development Goals (SDGs) 2030: sustainable consumption and production pattern. Throughout the entire food chain, the consumption stage by consumers is the largest contributor to food waste generation, accounting for approximately 35%. Food waste generation often results from food waste behavior among consumers, which can be driven by various factors such as the habit of purchasing excessive amounts of food, a lack of awareness about the importance of environmental preservation, insufficient knowledge on proper food processing and storage, and economic factors. Food waste behavior can have negative impacts on both the environment and the economy. One approach to understanding the phenomenon of food waste behavior is the Theory of Planned Behavior, particularly in the context of the intention to reduce food waste behavior among consumers. Through this literature study, the author aims to examine the intention to reduce food waste behavior based on the predictors of the Theory of Planned Behavior.